PERAN PEMERINTAH DALAM PERLINDUNGAN HUKUM TERHADAP PEKERJA OUTSOURCING DI PT. BALI DANA SEJAHTERA OLEH PT. BPD BALI - I Wayan Artana (Fakultas Hukum Universitas Dwijendra, 2020)
It is the duty of the Labor Office in an effort to provide protection to outsourced workers as an agency authorized to carry out supervision and enforcement of any violations of labor regulations by employers and workers who have not carried out firmly, especially in favor of employers and tend not to act fairly regarding the fulfillment of rights workers' rights. Therefore, the problem of outsourced workers often occurs, both in terms of wages or extension of the work contract. Based on the background above is: 1) How is the legal protection of outsourcing at PT Bali Dana Sejahtera which is employed at PT BPD Bali?; 2) What is the government role in legal protection for outsourced workers at PT Bali Dana Sejahtera which is employed at PT BPD Bali? The research method used in this paper is an empirical juridical approach. The authors in collecting data use techniques through interviews. Data processing is presented with descriptive qualitative techniques in the form of oral or written words from a subject that has been observed and has the characteristics that the data provided is original data that is not changed and uses a systematic and accountable ways. While the data analysis technique is done to solve the problems contained in the formulation of the problem by using descriptive data analysis that is describing in detail the social phenomena by describing and explaining data obtained from existing theories and the results of research in the field so that they are able to answer existing problems. It can be concluded that the form of protection that can be given is economic protection, namely protection of workers in the form of adequate income, including if workers are unable to work against their will, social protection that is protection of workers in the form of occupational health insurance, and freedom of association and protection of the right to organize, and technical protection, namely work protection in the form of work security and safety. The government role in legal protection for outsourced workers in PT. Bali Dana Sejahtera which is employed at PT. BPD Bali is intervening in labor relations to minimize industrial relations disputes, supervise and take decisive action against all forms of exploitation of outsourced labor, oversee the application of work norms and K3 norms in outsourcing practices, so that there are guarantees from employers to always provide work protection and working conditions for workers and creating regularity in the outsourcing business. Keywords: The outsourcing role in a company